2021
DOI: 10.1111/liv.14784
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of dysfunctional CD56‐CD16+ NK cells in chronic hepatitis B patients

Abstract: Background & Aims: Natural killer (NK) cells are primary innate effector cells that play an important role in the control of human viral infections. During chronic viral infection, NK cells undergo significant changes in phenotype, function and subset distribution, including the appearance of CD56-CD16+ (CD56-) NK cells, previously identified in chronic human immunodeficiency virus (HIV) and hepatitis C virus infection. However, the presence of CD56-NK cells in the pathogenesis of chronic hepatitis B (CHB) rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 79 publications
(193 reference statements)
3
7
0
Order By: Relevance
“…By contrast, during chronic HBV (CHB) infection, NK cells display fewer activating and more inhibitory receptors and lose effector functions, particularly the capacity to secrete cytokines [ 72 , 73 ]. These findings are consistent with recent studies describing the expansion of dysfunctional CD56 - CD16 + NK cells and a transcriptional NK cell profile similar to that of exhausted T cells in CHB patients [ 74 , 76 ]. NK cell dysfunction in CHB patients is mediated by elevated expression of immunosuppressive cytokines such as IL-10 and TGF-β [ 75 , 76 ].…”
Section: Viral Infections Of the Liversupporting
confidence: 93%
“…By contrast, during chronic HBV (CHB) infection, NK cells display fewer activating and more inhibitory receptors and lose effector functions, particularly the capacity to secrete cytokines [ 72 , 73 ]. These findings are consistent with recent studies describing the expansion of dysfunctional CD56 - CD16 + NK cells and a transcriptional NK cell profile similar to that of exhausted T cells in CHB patients [ 74 , 76 ]. NK cell dysfunction in CHB patients is mediated by elevated expression of immunosuppressive cytokines such as IL-10 and TGF-β [ 75 , 76 ].…”
Section: Viral Infections Of the Liversupporting
confidence: 93%
“…Consistently, in our study, we confirmed the expansion of the CD56 neg NK cell population. Similarly, expansion of CD56 neg NK cells has also been observed during infections with other viruses, including HCV, cytomegalovirus, Epstein-Barr virus, and HBV (36)(37)(38)(39). More recently, unconventional CD56 neg NK cells were shown to result from aberrant maturation of conventional NK cells, and a high frequency of CD56 neg NK cells was found to be associated with adverse clinical outcomes in acute lymphoblastic leukemia (40).…”
Section: Discussionmentioning
confidence: 88%
“…Our results suggested that the frequency of NK cells was reduced under the condition of pregnancy. Studies have reported that NK cells play a major role in the occurrence of CHB ( 7 10 ). HBV virus can damage and inhibit the function of NK cells ( 11 ).…”
Section: Discussionmentioning
confidence: 99%